The effect of synergistic pollution and carbon reduction in the digital economy: Quasi-experimental evidence from Chinese cities - Yin, Bibo; Kuang, Ping; Deng, Xinhui (Frontiers in Energy Research, 2023)
Introduction: The digital economy plays a crucial role in achieving synergistic reduction in air pollutants and carbon emissions. Methods: A super-efficiency slack-based model with undesirable outputs was applied to systematically calculate the efficiency of synergistic air pollutants and carbon emissions governance (ESACG). This study used the difference-in-differences (DID), propensity score matching-DID, quantile DID methods and generalized random forest model to empirically test the impact and its heterogeneity of the digital economy on the ESACG, with the establishment of the National Big Data Comprehensive Pilot Zone as a quasi-natural experiment. Results: 1) The digital economy significantly improved the ESACG by optimizing industrial structure in source management, improving energy utilization efficiency in process control, and promoting green technological innovation in end blocking. The digital literacy of talent and digital financial support strengthened its enhancing effect, but the digital infrastructure was insignificant. 2) The digital economy significantly enhanced the ESACG in the cross-regional and regional demonstration zones but inhibited it in the pioneering zones. Its impact on the ESACG in big data infrastructure-integrated development zones was insignificant. 3) Between the 25th and 90th quantiles, there was an asymmetric inverted U-shaped influence of the digital economy on the ESACG, with no discernible impact at the 10th quantile. In cities with better economic development and technological innovation, the contribution of the digital economy to the ESACG was more significant. Discussion: It is necessary to continuously advance the construction of existing pilot zones, steadily expand their coverage, and differentiate between harnessing the experiences of reducing pollution and carbon emissions to formulate strategies for synergistic regional governance.